MULTIPERAN PEREMPUAN DAN KETAHANAN RUMAH TANGGA: ANALISIS HUKUM ISLAM TERHADAP PRAKTIK PEREMPUAN MODERN - Hanifah Vemilia Zia Azizah Sartono; Arif Husnul Khuluq (LPPM STAI Muhammadiyah Probolinggo, 2026)
Women are a key factor in maintaining household resilience. However, social developments in the modern era have given rise to the phenomenon of multiple roles among married women with children, which is often viewed as potentially disruptive to family stability. This study aims to analyze the impact of multiple roles on household resilience, the strategies employed to achieve household resilience, and the perspectives of Islamic law on this practice. This study employed a descriptive qualitative approach, with data collection techniques including interviews, observation, and literature review. The results indicate that women's multiple roles are not always detrimental to household integrity; instead, they can strengthen household stability provided they manage their roles effectively, manage their time effectively, and receive family support. From an Islamic legal perspective, multiple roles are permissible (mubah) as long as household obligations are met and in accordance with sharia. This research provides a legal basis for modern women to balance social and family roles. The primary contribution of this research lies in its empirically based study of modern women's practices, analyzed from an Islamic legal perspective, with a focus on strengthening household resilience.